Assessing nanotoxicity of food-relevant particles: a comparative analysis of cellular responses in cell monolayers versus 3D gut epithelial cultures - Gautam, Archana (2024)
Engineered nanoparticles (NPs) are extensively used in the food industry, yet safety concerns remain. The lack of validated methodologies is a bottleneck towards resolving this uncertainty. Hence, the current study aims to compare two cell models by examining the toxicological impacts of two food-relevant NPs (SiO2 and Ag) on intestinal epithelia using monolayer Caco-2 cells and full-thickness 3D tissue models of human small intestines (EpiIntestinalTM). Comprehensive characterization and dosimetric analysis of the NPs were performed to determine effective doses and model realistic exposures. Neither genotoxicity nor cytotoxicity were detected in the 3D tissues after NP treatment, while the 2D cultures exhibited cytotoxic response from Ag NP treatment for 24 hr at 1 g/ml. Hyperspectral imaging and transmission electron microscopy confirmed uptake of both NPs by cells in both 2D and 3D culture models. Ag NPs caused an increase in autophagy, whereas SiO2 NPs induced increased cytoplasmic vacuolization. Based on realistic exposure levels studied, the 3D small intestinal tissue model was found to be more resilient to NP treatment compared to 2D cell monolayers. This comparative approach towards toxicological assessment of food relevant NPs could be used as a framework for future analysis of NP behavior and nanotoxicity in the gut.